APLIKASI PEMBELAJARAN INTERAKTIF PENGENALAN PAKAIAN ADAT SULAWESI MENGGUNAKAN AUGMENTED REALITY - Ahmad Thariq (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Indonesia's cultural diversity, especially traditional clothing from Sulawesi, is a heritage that needs to be preserved. Sulawesi has a variety of traditional clothing that reflects the cultural richness and identity of its people. However, a lack of understanding and access to information about traditional clothing often poses a challenge to cultural preservation efforts. The objective of this research is to develop an AR-based learning application that can help users learn about traditional Sulawesi clothing in an interactive manner. The application is designed to allow users to view three-dimensional models of traditional clothing, interact with visual elements, and access educational information about the philosophy and history of the clothing. The development method used in this study is MDLC. The stages include concept development, UI/UX design, material collection, application development, functional testing, and application distribution. Data was collected through literature studies, observations, and trials with users. The research findings indicate that AR-based applications can serve as an effective educational tool, raising public awareness of Sulawesi's cultural heritage to support the preservation of Indonesia's cultural heritage, particularly in Sulawesi. Additionally, these applications can enhance users' understanding of traditional Sulawesi attire in a more engaging and interactive manner compared to conventional methods, thereby fostering greater user involvement and interest in learning about local culture through immersive visual experiences.